Comparative studies on the efficacy of lincomycin and bacitracin for the control of necrotic enteritis in broiler chickens - Elkomy, Ashraf A.; Farag, Enas; El Gharbawy, El Shahat I.; Elbadawy, Mohamed (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The present study was conducted to evaluate the efficacy of lincomycin and/or bacitracin for control of experimentally-induced Clostridium perfringens (CP) infection in broiler chickens. Methods: A total of 100 one-day-old Cobb-mixed chicks were divided into five groups (A, B, C, D and E, each of 20 bird). At the 15th day of age, all birds (except group A) were inoculated orally with CP broth culture (109 CFU/mL). Two days later, drugs were orally administered once daily for five consecutive days as follow; Group A and B were left untreated. Group C, D, and E were treated with lincomycin (0.5 g/l), bacitracin (100 mg/l), lincomycin and bacitracin, respectively. The efficacy of used drugs was estimated based on clinical symptoms, body weight, weight gain, feed conversion rate. Hematobiochemical changes were also determined. Results: Necrotic enteritis in broiler chickens induced a significant decrease in body weight, weight gain, erythrocytic count, hemoglobin content, PCV %, serum proteins, catalase, and superoxide dismutase. Additionally, a marked decrease in serum lipids was obtained. Furthermore, a significant increase in feed conversion rate, leukocytic count, phagocytic activity, phagocytic index, serum total globulin, γ globulin and malondialdehyde coupled with a marked increase in β and α globulins were determined. Medication of infected broilers with lincomycin and/or bacitracin improved clinical signs and reduced mortality rate to 8, 6 and 2%, respectively, as well as restored the performance and hematobiochemical alterations. Conclusions: a combination of lincomycin and bacitracin was of considerable value for the control of necrotic enteritis in broiler chickens.